Pengaruh Model Pembelajaran Numbered Head Together (NHT) Terhadap Aktivitas Belajar Siswa Pada Mata Pelajaran Fiqih Kelas XI di MAN 1 Kota Bukittinggi - Hanifah Khairani; Darul Ilmi; Muhiddinur Kamal; Ulva Rahmi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The background to this research is that students lack enthusiasm and are less active in the Fiqh subjects taught by the teacher during learning. Lack of cooperation can trigger students to be active and discuss learning with their friends. Based on this, the researchers tried to offer a Numbered Head Together (NHT) Cooperative learning model. The formulation of the problem in this research is how much influence the Numbered Head Together (NHT) Cooperative Learning Model has on student learning activities in the Class XI Fiqh subject at MAN 1 Bukittinggi City. This research aims to determine how much influence the Numbered Head Together (NHT) Cooperative Learning Model has on student learning activities in the Class XI Fiqh subject at MAN 1 Bukittinggi City. The type of research used in this research uses quantitative research methods with a quasi-experimental approach. In this study, a nonequivalent control group design was used. The population in this research were all class XI students at MAN 1 Bukittinggi City. Sampling was carried out randomly and class XI IPS 2 was selected as the control class and class XI IPS 3 as the experimental class. The results of this research can be explained that there is an increase in the learning activity of experimental class students with the Numbered Head Together (NHT) model compared to learning in the control class without any treatment. Based on hypothesis testing, it is known that there are differences in fiqh learning activities between experimental class and control class students, namely based on the t-test, tcount = 3.491 and ttable = 1.66. Based on the results obtained, the value tcount > ttable so that H0 is rejected and H1 is accepted. This means that the Numbered Head Together (NHT) learning model influences students' fiqh learning activities.